Impact of resistance training on energy intake and appetite regulation for obese or overweight individuals: a systematic literature review - Soh, Kim Geok; Wang, Qiang; Gan, Wan Ying; Luo, Sheng Yao; Sun, He (Sociedad Revista de Psicologia del Deporte, 2024)
Individuals experiencing obesity or overweight conditions frequently encounter difficulties in managing their appetite. The sustained practice of resistance training over an extended duration presents a potential avenue for regulating appetite among this demographic. Despite the extensive examination of long-term resistance training in existing literature, a consensus on pertinent issues remains elusive, necessitating a comprehensive review. This paper aims to evaluate empirical studies examining alterations in energy intake and appetite among obese or overweight individuals engaging in prolonged resistance training regimens. Information was gathered from databases including EBSCOhost, Science Direct, PubMed, and Web of Science. Search queries were executed on Google Scholar and other sources, utilizing key terms pertinent to energy intake (or appetite), resistance training, and overweight (or obesity) for identifying relevant studies. A comprehensive evaluation of 38 full-text articles was conducted, resulting in the inclusion of eight articles in the review. The PEDro scale was utilized to assess bias and completeness risk, with no exclusion of any articles during this process. The impact of resistance training on energy intake in overweight or obese individuals was observed through sessions lasting 35–45 minutes conducted twice a week over a nine-month period. The exercise significantly influenced parameters such as energy intake, glucose levels, leptin concentrations, Homeostatic Model Assessment of Insulin Resistance (HOMA-IR), Neuropeptide Y (NPY), and adiponectin. However, no significant effects were noted on perceived fullness and hunger, ghrelin PP, or PYY. Resistance training has the potential to impact energy intake and appetite regulation in overweight or obese individuals. Further research is warranted, particularly in exploring its effects on female and adolescent populations, implementing a sample size calculation strategy, conducting comparisons across three intensities, and undertaking a comprehensive analysis of relevant variables.